PEMANFAATAN KECERDASAN BUATAN ARTIFICIAL INTELLIGENCE (AI) DALAM MEMBANTU KINERJA PEMBELAJARAN - Febrianti, Kareena Raudah; Azizah, Nur; Rusadi, Fadullah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The purpose of this study is to find out how students utilize artificial intelligence or AI in learning. The research method used is qualitative, namely in-depth interviews on the implementation of AI technology on campus as an approach method. The research sample we took was through IAIN Palangka Raya students from four existing faculties. From the results of the research that researchers have done, the use of AI has various benefits and problems for students. For example, students utilize AI to make it easier for them to find references, shorten their assignments, and increase their knowledge. However, the problem that occurs is that students tend to depend on AI in completing assignments, making reasoning difficult, and even becoming lazy in reading literature. The implication of this research is that students feel helped by the development of AI technology. It is hoped that this research can encourage better policies and strategies for implementing AI in the campus environment and can make a positive contribution in increasing the understanding and application of AI technology in students.